2009
DOI: 10.1038/ejcn.2009.38
|View full text |Cite
|
Sign up to set email alerts
|

Getting beyond outcomes: a realist approach to help understand the impact of a nutritional intervention during smoking cessation

Abstract: Objectives: This paper discusses the benefits that a 'realist' approach can bring to an outcome study using the example of a nutritional intervention offered as an adjunct to the existing smoking cessation programmes to limit post-cessation weight gain. Subjects and setting: Participants of a smoking cessation programme in areas of deprivation in the north, south and west of Glasgow. Results: A realist approach enabled the development of a framework able to investigate both implementation and outcomes of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Details of the selection process are provided in Figure 2. In two cases [27],[28], the article identified in the initial search provided a description of a realist evaluation associated with a randomized controlled trial. Additional information about these projects and application of the RE approach was sought by identifying additional publications pertaining to these trials [29]-[31].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the selection process are provided in Figure 2. In two cases [27],[28], the article identified in the initial search provided a description of a realist evaluation associated with a randomized controlled trial. Additional information about these projects and application of the RE approach was sought by identifying additional publications pertaining to these trials [29]-[31].…”
Section: Resultsmentioning
confidence: 99%
“…Articles retrieved for inclusion were published in the years between 2007 and 2013. Of the 14 studies identified, 6 were protocols that contained descriptions of proposed rather than completed research [28],[33]-[37]. In general, there did not appear to be any specific preference in terms of healthcare setting or type of knowledge translation intervention studied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations